Draft whole genome sequence of the cyanide‐degrading bacterium Pseudomonas pseudoalcaligenes CECT5344. (24th September 2012) - Luque‐Almagro, Víctor M.; Acera, Felipe; Igeño, Ma Isabel; Wibberg, Daniel; Roldán, Ma Dolores; Sáez, Lara P.; Hennig, Magdalena; Quesada, Alberto; Huertas, Ma José; Blom, Jochen; Merchán, Faustino; Escribano, Ma Paz; et al.
Summary: Pseudomonas pseudoalcaligenes CECT5344 is a Gram‐negative bacterium able to tolerate cyanide and to use it as the sole nitrogen source. We report here the first draft of the whole genome sequence of a P. pseudoalcaligenes strain that assimilates cyanide. Three aspects are specially emphasized in this manuscript. First, some generalities of the genome are shown and discussed in the context of other Pseudomonadaceae genomes, including genome size, G + C content, core genome and singletons among other features. Second, the genome is analysed in the context of cyanide metabolism, describing genes probably involved in cyanide assimilation, like those encoding nitrilases, and genes related to cyanide resistance, like the cio genes encoding the cyanide insensitive oxidases. Finally, the presence of genes probably involved in other processes with a great biotechnological potential like production of bioplastics and biodegradation of pollutants also is discussed.